Estudio de ingeniería y factibilidad para desarrollo de herramienta de inspección interna caliper para el oleoducto de crudos pesados OCP Ecuador S.A. - Boada Verdezoto, Andrea Katterine (2018)
In order to constantly monitor the status of the pipeline to take early actions, it was decided to start the development of this project, based on the engineering and feasibility study to develop an internal Caliper inspection tool for the OCP Ecuador S.A. pipeline. This tool is able to detect geometric deformations caused by landslides considered high incidence areas or by third parties. The construction of a basic prototype of Caliper was carried out, which contains several types of sensors and modules that allow obtaining necessary information to detect, locate geometric deformations present in the walls of the pipe. The Caliper stores the information in an internal memory to later extract the data and analyze them. To test the functionality of the Caliper prototype, the first phase of dry tests of the electronic and mechanical structure was carried out together to verify the behavior of the sensors. A dry test piping system was built, approximately 30 meters in length, this test system contains longitudinal and circumferential welds as joint tubes, defects such as dents, wrinkles, ovalities, bumps. Among the tests that were carried out were tests of distance traveled based on the odometric wheel, detection of defects with deformation sensors, angular position with a gyroscope and storage of information. The results obtained in these tests were favorable with 90% of the prototype's functionality and with a margin of error of less than 5%.